Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content: 1. The role of the social worker in dealing with family disintegration Mrs. Sarah Hamid Al-Ahmadi 2. Fashion designing simulating environmental art (the southern region) as one of the Small Enterprises to stimulate tourism according to the vision of 2030 for the Kingdom of Saudi Arabia Co-Prof. Randa Monier Elkherbawy 3. Cosmic justice between theory and practice in John Rawls’ philosophy Prof-lecturer Boussekek Abdelghani Ben Ali 4. The intellectual activities of the Maghreb cinematic discourse: Attempts to understand reality and its manifestations Dr. Elmahmoudi Tarek 5. The reality of Qualifying and Training Graduates of the Department of Library and Information Science - Sana’a University in line with the requirements of the labor market: Field study Dr. Merzah Ahmed Al-Assal 6. Climate change’s effects on women: Iraq as an example Asst-Teacher Ansam Ali Zghir 7. Commissive Illocutionary Acts Found in Na’ima Robert’s She Wore Red Trainers Mrs. Doa‘a Ali Mohammed Farhan Al-Sharabi , Prof. Abdusalam Mohammed Ghaleb Al-Ghrafy 8. Three Major Stages in the Historical Development of Translation Dr. Ahmed Mohamed Lemine El-Mokhtar